Adaptive duty cycle control–based opportunistic routing scheme to reduce delay in cyber physical systems - Xuemei Xiang; Wei Liu; Anfeng Liu; Neal N Xiong; Zhiwen Zeng; Zhiping Cai (International Journal of Distributed Sensor Networks)
Wireless sensor networks are the foundation of cyber physical systems. In loss and delay sensitive wireless sensor networks, there is much room for improving the performance of opportunistic routing scheme. In this article, an adaptive duty cycle control–based opportunistic routing scheme was put forward to improve the performance of the opportunistic routing scheme. Our main work is as follows: (a) the proposed duty cycle control–based opportunistic routing scheme implements the opportunistic routing in the duty cycle–based wireless sensor networks. Compared with the opportunistic routing scheme in the non-duty cycle mode, the duty cycle control–based opportunistic routing scheme can effectively reduce the energy consumption by 55.64%, although the performance in the delay is degraded. (b) Next, adaptive duty cycle control–based opportunistic routing scheme is proposed to reduce the delay of nodes in duty cycle control–based opportunistic routing. In adaptive duty cycle control–based opportunistic routing scheme, the node’s duty cycle is increased in the area where the energy has remaining, so that the network delay can be reduced without reducing the network lifetime. Compared with duty cycle control–based opportunistic routing scheme, the maximum end-to-end delay of the node in the network can be reduced by 69.83%.